On lingering and being last : race and sovereignty in the New World - Elmer, Jonathan, 1961- (UPCC book collections on Project MUSE., 2008)
In 'On Lingering and Being Last', Jonathan Elmer argues that the logic of sovereignty that emerged in early modern Europe and that limits our thinking today must be understood as a fundamentally racialized logic, first visible in the New World.